Physicochemical and sorptive properties of biochars derived from woody and herbaceous biomass. (September 2015) - Wang, Shengsen; Gao, Bin; Zimmerman, Andrew R.; Li, Yuncong; Ma, Lena; Harris, Willie G.; Migliaccio, Kati W.
Highlights: Prepare conditions affected biochar's physicochemical properties. Prepare conditions affected the sorption of As and Pb onto biochars. All the tested biochars removed As and Pb form aqueous solutions. Electrostatic interaction played an important role in biochar sorption. Abstract: It is unclear how the properties of biochar control its ability to sorb metals. In this work, physicochemical properties of a variety of biochars, made from four types of feedstock at three pyrolysis temperatures (300, 450 and 600 °C) were compared to their ability to sorb arsenic (As) and lead (Pb) in aqueous solutions. Experimental results showed that both feedstock types and pyrolysis temperature affected biochar's production rate, i.e., ratio of mass of biochar and biomass, thermal stability, elemental composition, non-combustible component (NCC) content, pH values, surface areas and thus their sorption ability to the two metals in aqueous solution. In general, the high temperature biochars had low O/C and H/C ratios, were more carbonized with larger surface area, and were more concentrated with alkaline cations. In addition, biochars made from woody feedstocks had larger surface area, but lower NCC contents than that made from grasses under the same conditions. Although all the tested biochars removed both As and Pb from aqueous solutions, they showed different sorption abilities because of the variations in properties. Statistical analyses suggested that feedstock type affected the sorption ability of the biochars to both As and Pb significantly ( p < 0.001). Pyrolysis temperature, however, showed little influence on biochar sorption of Pb in aqueous solutions. Statistical analyses also showed that electrostatic interaction played an important role in controlling the sorption of both As(V) and Pb(II) onto the biochar. Other mechanisms, such as precipitation and surface complexation, could also control the sorption of Pb(II) onto the biochars.